Oral manifestations of vitiligo - Anitha Nagarajan; Mahaboob Kader Masthan; Leena Sankari Sankar; Aravindha Babu Narayanasamy; Rajesh Elumalai (Wolters Kluwer Medknow Publications, 2015)
Background: Vitiligo is one of the disorder that has social impact . Both skin and mucous membrane show depigmentation in vitiligo. Depigmentation in oral cavity can be more easily observed and the patient can be given awareness regarding the condition if they are unaware of vitiligo elsewhere in their body and can be guided for treatment. Aim and objectives: The aim of this study is to determine the frequency of occurrence of oral mucosal vitiligo in vitiligo patients and to determine the most commonly involved oral mucosal site. Materials and methods: The study sample included 100 vitiligo patients. The patients of all age groups and both genders were included. Vitiligo patients associated with systemic conditions such as thyroid disorders, juvenile diabetes mellitus, pernicious anemia, Addison's disease were excluded in this study. Results: Out of 100 vitiligo patients 44 % male and 56% were female. The oral presentation of vitiligo in this study showed depigmentation of buccal mucosa in 5% of patients, labial mucosa in 5% of patients, palate in 8% of patients, gingiva in 2% of patients and alveolar mucosa 1% . Depigmentation of lip was seen in 42% of patients. Lip involvement refers to depigmentation of both the lips or either lip. Also vermilion border involvement was noted in majority of cases. In some cases, the depigmentation of lip extended to the facial skin also. Conclusion: In this study 55 patients out of 100 patients showed depigmentation in the oral cavity. Lip involvement was most common in this study showing about 42% of patients. Intraoral mucosal involvement was found in 21% of patients. Among intraoral mucosal site palate was common followed by buccal and labial mucosa, gingiva. Two patients had lip pigmentation as the only manifestation without any depigmentation in the skin.